Morphometric analysis of watersheds: A comprehensive review of data sources, quality, and geospatial techniques - Padala Raja Shekar; Aneesh Mathew (Watershed Ecology and the Environment)
The analysis of morphometric parameters plays a crucial role in understanding and managing watersheds, making it a fundamental component of hydrological investigations. This review paper talks about how important it is to objectively evaluate morphometric parameters, with a focus on the evaluation of basins' relief, linear, and areal parameters. However, it is noted that there is a lack of a distinct standard classification and implication for each parameter in some research publications. Furthermore, the range and categories of values for each morphometric parameter have not been adequately addressed in previous studies. Many papers state whether a particular parameter's resultant value is high or low without providing specific value ranges or associated implications. Also, it is emphasised that the accuracy and sources of digital elevation models (DEMs) affect how well morphometric parameter analysis works, even when DEMs with the same resolution are used. The existing literature demonstrates that determining the value of each morphometric parameter poses significant challenges. Moreover, verifying the first and second Horton's laws and assessing the correlations between morphometric parameters have been lacking in some articles. The main objective of this review article is to address these gaps by providing an in-depth study of each parameter's categorization, including the range of values, the level of input data quality, the data products generated, and the applicability of the fundamental Horton's laws. By doing so, this review aims to enhance the understanding of morphometric parameters, their value ranges, and the significance of their application in watershed analysis and management.